CLINICAL-LABORATORY AND MORPHOLOGICAL FEATURES OF THE INTESTINAL YERSINIOSIS IN CHILDREN - Nezgoda, I.I.; Havryliuk, A.O.; Naumenko, O.M.; Asaulenko, A.А.; Kholod, L.P.; Levytska, L.I.; Onofriichuk, O.S. (World of Medicine and Biology, 2019)
The article presents the results on the case histories retrospective analysis in 21 patients diagnosed with intestinal yersiniosis with a detailed study of the disease course with the clinical and anamnestic data analysis. The intestinal yersiniosis course was characterized by the mosaic of clinical symptoms and was accompanied by signs of intoxication syndrome, exanthema syndrome, lymphadenopathy, hepatosplenomegaly with the gastrointestinal tract lesions. Morphological and histological changes of internal organs in children with fatal outcome of the disease were characterized by uneven blood filling, swelling and hemorrhages in the mucous membrane of internal organs, dystrophic changes in parenchymal organs, formation of lymph nodes conglomerates with areas of necrosis. The obtained data indicate that fatal cases of intestinal yersiniosis were found in infants at the background of the complicated premorbid background and the concomitant pathology; they were running as a generalized form of infection (100%) with the development of complications and were caused by 0: 3 and 0: 9 serotypes of Y. еnterocolitica.
Keywords: intestinal yersiniosis; pathomorphological changes; histological studies; children